Semantic Analysis of the Synonymity of the Meaning of Khatama and Ṭaba'a in the Quran: Contextual Relevance for Contemporary Interpretation Studies - Ramadhani, Ramadhani; Nasution, Ismail Fahmi Arrauf; Faza, Asrar Mabrur; Armainingsih, Armainingsih; Harahap, Alwi Padly (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The synonymy of meaning between the words khatama and ṭaba'a in the Qur'an has become an important issue in semantic and exegesis studies. These two words are often understood to have similar meanings, namely to close, but have different contextual nuances. This study aims to analyze the semantic differences between khatama and ṭaba'a, and evaluate their relevance in the context of contemporary exegesis. The method used is a qualitative method with semantic-comparative analysis techniques. The results of the study show that khatama tends to be used to describe God's action in closing the heart permanently as a consequence of rejecting the truth, while ṭaba'a is more of a locking action that is oriented towards cause and effect. In the context of contemporary exegesis, this difference is relevant to understanding the dynamics of guidance and rejection of the truth in modern society. In conclusion, khatama and ṭaba'a are not entirely synonymous, but rather have specific contextual meanings. This study makes an important contribution in deepening the study of the semantics of the Qur'an and enriching the interpretation of exegesis with a contextual approach.